Free-standing polyelectrolyte membranes made of chitosan and alginate - Caridade, S. G. (2013)
Free-standing films have increasing applications in the biomedical field as drug delivery systems for wound healing and tissue engineering. Here, we prepared free-standing membranes by the layer-by-layer assembly of chitosan and alginate, two widely used biomaterials. Our aim was to produce a thick membrane and to study the permeation of model drugs and the adhesion of muscle cells. We first defined the optimal growth conditions in terms of pH and alginate concentration. The membranes could be easily detached from polystyrene or polypropylene substrate without any postprocessing step. The dry thickness was varied over a large range from 4 to 35 μm. A 2-fold swelling was observed by confocal microscopy when they were immersed in PBS. In addition, we quantified the permeation of model drugs (fluorescent dextrans) through the free-standing membrane, which depended on the dextran molecular weight. Finally, we showed that myoblast cells exhibited a preferential adhesion on the alginate-ending membrane as compared to the chitosan-ending membrane or to the substrate side.